A game of thrones [compact disc, unabridged] - Martin, George R. R. (Martin, George R. R. Song of ice and fire, 2011)
Long ago, an enigmatic event forever changed the seasons in Winterfell. Thus the land was blessed with lush summers and simultaneously cursed with harsh winters. Now, Winterfell's borders are being increasingly encroached, forcing the prominent Stark family to defend its kingdom from enemies both old and new, including the rival Lannister House and a legendary demon.